A randomized clinical trial of low dose single antibiotic- loaded cement versus high dose dual antibioticloaded cement in patients receiving a hip hemiarthroplasty after fracture: A protocol for the WHiTE 8 COPAL study. (2021) - Agni, N. R.; Costa, M. L.; Achten, J.; O'Connor, H.; Png, M. E.; Peckham, N.; Dutton, S. J.; Wallis, S.; Milca, S.; Reed, M.
No abstract available